IMPLEMENTASI PERATURAN DAERAH NOMOR 07 TAHUN 2011 TENTANG PAJAK HOTEL (Studi Kasus Pajak Rumah Kos -Kosan Di Kecamatan Tampan) - Andrika "; Sujianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Implementation of Regional Regulation No. 7 of 2011 Concerning Tax Hotel, in article I, paragraph 10 mentioned facilities services provider lodging, resort, including other related services free of charge, which includes motels, inns tourism hut, tourism guest house, guesthouse, inn, house stop, as well as boarding houses exceeded the number of rooms from 10 rooms hotel taxed.The purpose of this study was to determine the Implementation Regulation No. 7 of 2011 on Taxes (Tax Case Study Kos - Kosan In Sub Handsome) and to determine factors - factors inhibiting the Implementation Regulation No. 7 of 2011 on Taxes (Tax Case Study Kos - Kosan In Sub Handsome).The concept of the theory used is the theory of implementation according to George Edward III, namely: communication, resources, attitudes and bureaucratic structure. This study used qualitative research methods. In collecting the data, researchers use interviewing techniques, observation and study of literature.Based on the results of research conducted by the author in Pekanbaru District of Handsome, on the implementation of the Regional Regulation No. 7 of 2011 Concerning Taxes can be deduced that have not been implemented well, it is seen from the four indicators, namely communication, resources, disposition and bureaucratic structure. Factors Communication, communication factor emphasis on socialization and communication flow in providing information duties and functions of each member. Factor Human Resources, faced with conditions that are less employees. Disposition factor, based on the results of this study, it is still a lack of traction implementer in implementing regional regulation. Bureaucratic structures, in this case the Standard Operating Procedures (SOP) has been applied in accordance with the applicable rules, but the application is carried out by field officers are still lacking, it is because there are many who escaped the observation field officers so that there are many homeowners who do not obey boarding against regulations that have been made.Keywords: Implementation, Regional Regulations and Taxes